Pelatihan Pengembangan Aplikasi Mobile Menggunakan Flutter pada SMAS Wiyata Dharma - Halim, Apriyanto; Pipin, Sio Jurnalis; Tanti, Tanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
SMAS Wiyata Dharma is a school in the city of Medan and has been established since November 14 1985. This school is located on Jalan Wahidin No. 31 Medan, North Sumatra Province. This school has currently received an A accreditation rating. This school generally not only provides educational curriculum lessons but also provides learning related to computer science which can help students prepare themselves for the outside world. One of the lessons in computer science, namely mobile apps and the most widely used programming language is the Flutter programming language developed by Google. Through collaboration with Mikroskil University, SMAS Wiyata Dharma students are equipped with the ability to create mobile applications using Flutter in collaboration. This training activity lasted for 2 days and was carried out in the Mikroskil University computer laboratory. During this training activity, students were given pre-test questions, material and case studies, as well as post-tests and feedback at the end of the training. From the results of the pre-test and post-test, it can be seen that there is an increase in students' understanding of the results of the service carried out and from the feedback that has been shared with students, it can be seen that all students agree that the training carried out is in line with the students' expectations.